In vitro antimicrobial activity of linezolid tested against vancomycin-resistant enterococci isolated in Brazilian hospitals - Adriana O. Reis; Julio C. R. Cordeiro; Antonia M.O. Machado; Helio S. Sader (Brazilian Journal of Infectious Diseases)
The emergence of vancomycin-resistant enterococci (VRE) has been described recently in Brazil. This is in contrast to the USA and Europe, where the VRE appeared in the late 1980s. The progressive increase in VRE isolation poses important problems in the antimicrobial therapy of nosocomial infections. Treatment options and effective antimicrobial agents for VRE are often limited and the possibility of transfer of vancomycin genes to other Gram-positive microorganisms continues. In the search for antimicrobial agents for multiresistant Gram-positive cocci, compounds such as linezolid and quinupristin/dalfopristin have been evaluated. The present study was conducted to evaluate the in vitro activity of the oxazolidinone linezolid and 10 other antimicrobial agents, including quinupristin-dalfopristin, against multiresistant enterococci isolated in Brazilian hospitals. Thirty-three vancomycin resistant isolates (17 Enterococcus faecium and 16 E. faecalis), were analyzed. Strains were isolated from patients at São Paulo Hospital, Oswaldo Cruz Hospital, Hospital do Servidor Público Estadual, Santa Marcelina Hospital, Santa Casa de Misericórdia de São Paulo, and Hospital de Clínicas do Paraná. The samples were tested by a broth microdilution method following the National Committee for Clinical Laboratory Standards (NCCLS) recommendations. All isolates were molecular typed using pulsed-field gel electrophoresis (PFGE). Linezolid was the most active compound against these multiresistant enterococci, showing 100% inhibition at the susceptible breakpoints. Quinupristin/dalfopristin and teicoplanin showed poor activity against both species. The molecular typing results suggest that there has been interhospital spread of vancomycin resistant E. faecium and E. faecalis among Brazilian hospitals. The results of this study indicate that linezolid is an appropriate therapeutic option for the treatment of vancomycin-resistant enterococci infections in Brazil.